Analisis Mutu Pembelajaran Praktikum Kebidanan Sebagai Upaya Peningkatan Pencapaian Kompetensi Program Studi Diploma III Kebidanan STIKES Maharani Malang - Sumiatun, Sumiatun (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
This research is description of learning practicum instructors, that includes the planning, implementation and evaluation. In this research uses qualitative descriptive qualitative method based on empiric and normative approach. Data collection using interviews, observation and documentation studies. Data analysis using qualitative data analysis according to Miles and Huberman, continued with the SWOT analysis. The results showed that the planning of learning practicum instructors include syllabus, RPP, practicum instructors guide yet all lecturer learning practicum instructors, arranges the implementation of standards for comparison with students not yet appropriate faculty, not done prior to the implementation of learning nor pretest post tests after learning practicum instructors. As for the evaluation study has not yet been implemented optimally, as yet the existence of the document value for student practicum instructors. The quality of learning practicum instructors as seen from existing indicators i.e. reliability, responsiveness, assurance of learning practicum instructors, empathy and appearance have not been optimal.